COVID-19 vaccination in rural India: a battle to be won! - Sharma, Neha; Panda, Pragyan Swagatika; Dewan, Manasvee; Banerjee, Priyanka (International Journal Of Community Medicine And Public Health, 2021)
As of 22nd July 2021, 13.3% of world’s population are fully vaccinated and 26.8% of world’s population have received at least one dose of COVID-19 vaccine. COVID-19 vaccination drive was launched in India on 16th January 2021 with two government approved vaccines Covishield® and Covaxin®. About 65.53% of India’s population resides in rural areas. As vaccination is progressing, a gap (of number of vaccines administered) between urban and rural vaccination centers is clearly becoming evident. By mid-May, 30.3% of India’s urban population had received at least one dose of the vaccine compared to 19.2% in semi-urban areas, 15.1% in semi-rural areas and just 12.7% in rural areas. Vaccine roll out in rural areas is adversely affected probably because of unequal access in rural area, vaccine hesitancy due to misinformation and myths being circulated through social media and low educational status of rural population as compared to the urban peers. A successful COVID-19 vaccination drive depends on maximum possible coverage. Through this manuscript we aim to draw attention to objective and feasible strategies in order to bridge the existing urban-rural vaccination gap.